Remaking Muslim Lives: Everyday Islam in Postwar Bosnia and Herzegovina - Lived Islam: Colloquial Religion in a Cosmopolitan Tradition (American Journal of Islam and Society, 2021)
• Remaking Muslim Lives: Everyday Islam in Postwar Bosnia and Herzegovina (by David Henig)• Lived Islam: Colloquial Religion in a Cosmopolitan Tradition (by Kevin Reinhart)